Identification of novel inhibitors against UDP‐galactopyranose mutase to combat leishmaniasis. Issue 3 (10th November 2017) - Kashif, Mohammad; Tabrez, Shams; Husein, Atahar; Arish, Mohd; Kalaiarasan, Ponnusamy; Manna, Partha P.; Subbarao, Naidu; Akhter, Yusuf; Rub, Abdur
Abstract: Leishmania, a protozoan parasite that causes leishmaniasis, affects 1‐2 million people every year worldwide. Leishmaniasis is a vector born disease and characterized by a diverse group of clinical syndromes. Current treatment is limited because of drug resistance, high cost, poor safety, and low efficacy. The urgent need for potent agents against Leishmania has led to significant advances in the development of novel antileishmanial drugs. β‐galactofuranose (β‐Galf) is an important component of Leishmanial cell surface matrix and plays a critical role in the pathogenesis of parasite. UDP‐galactopyranose mutase (UGM) converts UDP‐galactopyranose (UDP‐Galp) to UDP‐galactofuranose (UDP‐Galf) which acts as the precursor for β‐Galf synthesis. Due to its absence in human, this enzyme is selected as the potential target in search of new antileishmanial drugs. Three dimensional protein structure model of Leishmania major UGM ( Lm UGM) has been homology modeled using Trypanosoma cruzi UGM ( Tc UGM) as a template. The stereochemistry was validated further. We selected already reported active compounds from PubChem database to target the Lm UGM. Three compounds (6064500, 44570814, and 6158954) among the top hit occupied the UDP binding site of UGM suggested to work as a possible inhibitor for it. In vitro antileishmanial activity assay was performed with the top ranked inhibitor, 6064500. The 6064500 molecule has inhibited the growth of Leishmania donovani promastigotes significantly. Further, at similar concentrations it has exhibited significantly lesser toxicity than standard drug miltefosine hydrate in mammalian cells. Abstract : In this study, we have selected UDP‐galactopyranose mutase (UGM), an enzyme involved in the synthesis of β‐Galactofuranose (β‐Galf), a major component of leishmanial membrane. Due to its absence in human, this enzyme has been targeted to search new antileishmanial drugs. Three dimensional model of Leishmania major UGM (LmUGM) has been generated using Trypanosoma cruzi UGM (TcUGM) as template and screened for reported active compounds from PubChem database to target it. Inhibitor having pubchem id: 6064500 has been proven as the best screened ligand of Lm‐UGM which was further validated by in vitro antileishmanial activity assay. It has exhibited comparatively and significantly lesser toxicity than miltefosine hydrate (known antileishmanial drug) in mammalian cells when treated with the same concentrations. This is the first study targeting Lm‐UGM for the screening of the proposed potential inhibitors to treat leishmaniasis in the best of our knowledge.